2019
DOI: 10.3892/ol.2019.10779
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary malignant neoplasms: A case report and literature review

Abstract: Until recently, few cases of three or more malignant tumors in one patient have been reported. Owing to the high incidence rate of these tumors, the improvement in cancer diagnosis and treatment, and the extension of patient survival time, the incidence of reported multiple primary malignant neoplasms has gradually increased. The present study reported the case of a 57-year-old man with non-small cell lung cancer combined with B-Raf proto-oncogene serine/threonine kinase V600E mutation, gastrointestinal stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Cancer survival has significantly improved; however, patients with cancer with a longer lifespan are at a higher risk of developing SPCs. A study revealed that the risk of SPCs was higher in cancer survivors than in the general population, with a 3.8% higher probability of developing metachronous SPCs within a median follow-up period of 2.5 years, and that the incidence increased over time with a 10-year cumulative risk of SPCs reaching 13% for patients diagnosed with cancer between the ages of 60 and 69 years [ 5 ]. Therefore, lung cancer survivors have increased chances of developing SPCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer survival has significantly improved; however, patients with cancer with a longer lifespan are at a higher risk of developing SPCs. A study revealed that the risk of SPCs was higher in cancer survivors than in the general population, with a 3.8% higher probability of developing metachronous SPCs within a median follow-up period of 2.5 years, and that the incidence increased over time with a 10-year cumulative risk of SPCs reaching 13% for patients diagnosed with cancer between the ages of 60 and 69 years [ 5 ]. Therefore, lung cancer survivors have increased chances of developing SPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the development of chest computed tomography has improved the early diagnosis of lung cancer [ 1 ], and precision medicine with individualized and molecularly targeted therapy has improved the survival of patients with lung cancer [ 2 ]. Evidence shows that cancer survivors are at an increased risk of second primary cancers (SPCs) [ 3 , 4 ], and the incidence of SPCs has increased over time with a 10-year cumulative risk reaching as high as 13% for patients diagnosed with cancer at the age between 60 and 69 years [ 5 ]. A study used the Surveillance, Epidemiology, and End Results (SEER) 13 registry to examine the multiple primary standardized incidence ratio and risk between January 2004 and December 2010 for patients with stage Ia non-small cell lung cancer (NSCLC), and the results showed that 1431 (11.68%) of 12,246 patients had SPCs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike isolated occurrences, the pathogenesis of multiple malignancies may be linked to specific genetic defects detectable by nextgeneration sequencing. 15 Still, standard treatments for MPMTs are not well established. Parameters to consider in treatment planning include certain tumor-specific (stage, biologic behavior) and patient-related variables (age, physical condition, life expectancy, and comorbidities).…”
Section: Discussionmentioning
confidence: 99%
“…Because GIST does not respond to conventional chemotherapy and radiation therapy, the gold standard for the treatment of GIST is surgical resection[ 5 ]. In addition, the use of Imatinib mesylate, a selective tyrosine kinase receptor inhibitor (TKI), significantly reduced the morbidity and mortality associated with GIST[ 6 - 8 ]. GIST metastasis usually occurs in the liver (28%), mesentery and omentum (30%), and less often in the lungs (7%), subcutaneous tissue (4.7%), and lymph nodes (4.7%)[ 9 , 10 ], whereas GIST bone metastasis is very rare (only 0.47%)[ 11 ].…”
Section: Introductionmentioning
confidence: 99%